2016
DOI: 10.3390/ijerph13111170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Research of the Effects of Longitudinal Speed Reduction Markings on Driving Behavior: A Driving Simulator Study

Abstract: The objective of this paper is to explore the effects of longitudinal speed reduction markings (LSRMs) on vehicle maneuvering and drivers’ operation performance on interchange connectors with different radii. Empirical data were collected in a driving simulator. Indicators—relative speed change, standard deviation of acceleration, and gas/brake pedal power—were proposed to characterize driving behavior. Statistical results revealed that LSRMs could reduce vehicles’ travel speed and limit drivers’ willingness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…As no similar studies have been found, making it impossible to compare the results obtained, it can be stated that the speed-reduction effect of the wider marks seen here is in line with the results of somewhat similar experiments about the effects of longitudinal speed reduction markings [26,27], and the consequences of implementing, or not, longitudinal road markings [29][30][31]. The speed-reducing effect may contribute to a reduction in the number of accidents associated with the implementation of wider longitudinal road markings [9,25,28] or the narrowing of lanes [6].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…As no similar studies have been found, making it impossible to compare the results obtained, it can be stated that the speed-reduction effect of the wider marks seen here is in line with the results of somewhat similar experiments about the effects of longitudinal speed reduction markings [26,27], and the consequences of implementing, or not, longitudinal road markings [29][30][31]. The speed-reducing effect may contribute to a reduction in the number of accidents associated with the implementation of wider longitudinal road markings [9,25,28] or the narrowing of lanes [6].…”
supporting
confidence: 83%
“…Longitudinal speed reduction markings are discontinuous longitudinal markings 30 cm wide painted next to the edgeline road markings, on the inside of the lane. Ding et al [26] and Zhao et al [27] studied their effect on connectors through driving simulation, obtaining the results that LSRMs could reduce vehicles' travel speed and limit drivers' willingness to increase speed, but effects depend on the radius and on the position of the vehicle along the connector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relative speed contrast (δ) shows the overall speed deceleration in the tunnel entrance and exit zones [15,30,41]…”
Section: Resultsmentioning
confidence: 99%
“…However, the evaluation on a driving Journal of Advanced Transportation simulator did report an impact of additional road markings on the lateral positioning of the vehicle. Ding et al carried out several driving simulator studies on this subject [19][20][21]. e studies were based on an analysis comprising vehicle operations and drivers' psychological and physical reactions.…”
Section: Road Markings As a Measure For Speed Reduction And Speed Limitmentioning
confidence: 99%
“…Ding et al explored the effects of longitudinal speed reduction markings on vehicle manoeuvring and drivers' operation performance on interchange connectors of different radii (50 m, 80 m, and 100 m) [21]. Using a driving simulator, the authors created two connectors of interest: one with and one without road marking measures.…”
Section: Road Markings As a Measure For Speed Reduction And Speed Limitmentioning
confidence: 99%